Sistem Penerangan Jalan Umum Berbasis IoT (Internet Of Things) - Robby J. Arung Laby; Andrew Joewono; Peter Rhatodirdjo Angka (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2021)
Public street lighting (PJU) is important as a public facility, which must be considered so that the system remains well maintained and optimal. Sometimes the condition of the lamp is not known the state of the system, because it is located in a location that is not directly accessible. Solution to overcome these problems using the Internet of Things (IOT), to monitor the condition of PJU equipment that is integrated with the internet network.This tool uses a 12 VDC battery, as the main energy source to operate the entire system. Solar panels will be input for energy for the charging process on the battery and also the lighting process by the PJU lights. This tool uses a microcontroller Wemos D1 Mini to control the system and connecting to the web server. ACS 712 current sensor and voltage sensor as parameters for monitoring the state of the PJU system, during the process of charging and supplying to the PJU lights.To ensure the system functions, measurements and tests are carried out, which include: Measurement of voltage and current from the solar panel for the process of charging to the battery as well as measurement of voltage and current from the battery when charging and discharging; Measurement of voltage and current of LED lights as lighting; Measurement of PIR sensor response time to distance and range distance; and Testing system monitoring on Android applications, as a whole system test.This tool is able to work automatically in the charging process and also the lighting process which is triggered based on the solar panel output voltage by the BCR, and the system can adjust the intensity of the lighting with PIR sensor parameters. The monitoring system can function in real time on an android smartphone.